Inovasi Pengendalian Hama Terpadu dengan Perangkap Hama Feromon Sex dan Yellow Sticky Trap pada Kelompok Tani Golo Curu Permai - Jessyca Putri Choirunnisa; Devi Liana; Muhammad Noor Ariefin; Rizki Adiputra Taopan; Defiyanto Djami Adi; Elfrida Knaofmone; Tri Astuti (Institut Pertanian Bogor, 2025)
Excessive use of pesticides leadsesidue that pose a danger to humans and the environment, and results in increased resistance and resurgence of pests in plants. The application of integrated pest management (IPM) technology, including sex pheromone traps and yellow sticky traps, has never been implemented by the Golo Curu Permai farmer group. The objectives of this activity were to was to reduce pesticide usage and to enhance the knowledge and skills of farmer groups regarding environmentally friendly pest control methods. The activity was conducted with at the Golo Curu Permai farmer group in Karot Village, Langke Rembong District, Manggarai Regency and conducted in July 2023 involving a total of 25 participants. The stages of the activity included a field survey, socialization, implementation, and evaluation. Evaluation was conducted by comparing the results of pre-test before the training and the post-test after training. The results of this activity indicated that the farmers skill in the farmer group, after participating in the training making and applying sex pheromone traps and yellow sticky traps, improved from 58 to 83%.